Inclusive and Generative Possibilities of Precedent Analysis in Architectural Education (EAAE Annual Conference Proceedings, 2023)
This study focuses on the contribution of precedent analysis to design thinking via the framework provided by the “device” and “material” relationship. Elucidated first by the formalist tradition of literary criticism known as Russian Formalism, the “device and material relationship” is explored as a viable framework for understanding and analysing architectural form.